2011
DOI: 10.1002/jssc.201100359
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of vinblastine and its monomeric precursors vindoline and catharanthine in Catharanthus roseus by capillary electrophoresis–mass spectrometry

Abstract: Catharanthus roseus is an important dicotyledonous medicinal plant that contains various anticancer components, such as vinblastine (VLB) and its monomeric precursors (vindoline and catharanthine). A capillary electrophoresis-mass spectrometry (CE-MS) approach for the simultaneous determination of three components was developed in this work. Baseline separation for three components was achieved by using a running buffer consisting of 20 mM ammonium acetate and 1.5% acetic acid in <20 min. Quantification of thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…The analysis of vinca alkaloids has been carried out on plant extracts, [398][399][400][401][402][403] pharmaceutical formulations, 316,404 biological samples 358,359,[405][406][407][408][409][410][411][412][413][414][415][416][417][418][419][420]421 and environmental samples. 18,19,134,307,422 Vinca alcaloid extraction from plants was generally performed by ultrasound in acid media followed by LLE.…”
Section: Antitubulin Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of vinca alkaloids has been carried out on plant extracts, [398][399][400][401][402][403] pharmaceutical formulations, 316,404 biological samples 358,359,[405][406][407][408][409][410][411][412][413][414][415][416][417][418][419][420]421 and environmental samples. 18,19,134,307,422 Vinca alcaloid extraction from plants was generally performed by ultrasound in acid media followed by LLE.…”
Section: Antitubulin Agentsmentioning
confidence: 99%
“…18,19,134,307,422 Vinca alcaloid extraction from plants was generally performed by ultrasound in acid media followed by LLE. 45,[398][399][400][401] CE methods are scarcely reported for the determination of vinca alkaloids. A CE-UV method in non-aqueous conditions (NACE) allowed the separation of ten different vinca alkaloids in less than 10 min.…”
Section: Antitubulin Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…C. roseus has been used in traditional medicine in tropical and subtropical countries for the treatment of diabetes, hypertension, bleeding, scurvy, toothaches, and others from ancient time. [7] At the moment in vivo and in-vitro studies have demonstrated hypoglycemic, antihypertensive, anti-bacterial, anti-malarial, antiarrhythmic and other properties of C. roseus [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Ph.) and its variations like, HPLC-UV-detector [19,21,22], HPLC-with electrochemical detector [23][24], HPLC-isotope dilution thermospray mass spectrometry [25], and also methods like thin layer chromatography [7,19,26], liquid chromatography with mass spectral detection [21,27,28], capillary zone electrophoresis-mass spectrometry [20], capillary electrophoresis-mass spectrometry [11,29], radio-immune analysis [30,31] etc. Many of these methods are characterized by highly labor intensive, the high cost of equipment's, long duration of analysis time, as well as usually highly toxic chemicals, are required for an analysis procedure.…”
Section: Introductionmentioning
confidence: 99%